Characterization of the starch from pompo rayado banana (Mussa Manini) (Revista de Investigaciones Universidad del Quindío, 2022)
In this work, the characterization of the starch of striped pompo plantain extracted by the wet method was carried out. The material obtained was characterized according to its physicochemical properties such as moisture content, crude fiber and amylose/amylopectin ratio, and additionally its functional properties were studied: whiteness index (IB), water absorption index (IAA), water solubility index (ISA) and swelling power (PH). The results indicate that the amylose percentage was approximately 30.2%, a percentage within the range found for musaceae, since the amylose content depends on the botanical origin. On the other hand, it presents a high fiber content of 6.68%, higher than that found for other varieties of plantain, which are between 2.5 - 4.0%. The study of the functional properties of the material obtained shows a higher whiteness index compared to other musaceae. The values for IAA that are accepted by FAO range from 0.82 to 15.52. However, for ISA, low indexes close to 0.333 were found. The PH is a parameter that goes hand in hand with the IAA and, consequently, shows the same behavior, which made it possible to establish that the starch to be treated was found to be within the ranges considered to be of good quality.
Keywords: plantain; Musaceae; starch; amylose; functional properties